(untitled) (Biological Sciences - PJSIR, 2000)
Sesamum indicum DC (sesame)seedscontainedmoisture4.7%andlipids53.9%.The lipidswerefractionated into neutral lipids (96.3%) and polar lipids (3.7%) by thin layer chromatography. The neutral lipids identified were hydrocarbons (0.3%),sterol esters(0.7%),triacylglycerols(80.6%),freefattyacids(2.1%),l,3-diacylglycerols(3.5%),l,2-diacylglycerols (4.7%), sterols (1.9%) and monoacylglycerols (2.5%). The polar lipids were phosphatidylethanolamines (0.6%), phos- phatidylcholines(1.3%),lysophosphatidylethanolamines(0.4%),lysophosphatidyJcholines(0.5%)andphosphatidlinositols (0.9%).The fatty acidsrangeofalltheesterifiedlipidswas(CI2:0-C20:0) showinghigherpercentagesofsaturatedfattyacids except intriacylglycerols. The majorfatty acidswerepalmitic,stearic,oleicandlinoleic acids.